2004
DOI: 10.2139/ssrn.504482
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and Economic Growth in Latin American Countries: A Panel Data Approach

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
157
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(174 citation statements)
references
References 44 publications
11
157
1
5
Order By: Relevance
“…As Chen and Chiou-Wei [13] state, the causal relationship between tourism and economic growth is not stable, and there might not be a unique relationship type among GCC countries. In this sense, Eugenio-Martin, Morales, and Scarpa [40], Chang, Khamkaev, and McAleer [41], Leitão [26], Tavares and Leitão [27], Chou [37], and Tugcu [39] in their empirical investigation argued that, depending on different dynamics, such as economic and political structures, trade openness, initial tourism conditions, investment rate, sectorial linkages, and historical background of the countries, this relationship may vary. Therefore, different studies could show different results in these countries in the context of tourism-led growth, even for the same sample.…”
Section: Panel Causality Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As Chen and Chiou-Wei [13] state, the causal relationship between tourism and economic growth is not stable, and there might not be a unique relationship type among GCC countries. In this sense, Eugenio-Martin, Morales, and Scarpa [40], Chang, Khamkaev, and McAleer [41], Leitão [26], Tavares and Leitão [27], Chou [37], and Tugcu [39] in their empirical investigation argued that, depending on different dynamics, such as economic and political structures, trade openness, initial tourism conditions, investment rate, sectorial linkages, and historical background of the countries, this relationship may vary. Therefore, different studies could show different results in these countries in the context of tourism-led growth, even for the same sample.…”
Section: Panel Causality Analysismentioning
confidence: 99%
“…Eugenio-Martin, Morales and Scarpa [40] investigated the relationship between tourism and economic growth in 21 Latin American countries using GMM dynamic panel data analysis, over the period [1985][1986][1987][1988][1989][1990][1991][1992][1993][1994][1995][1996][1997][1998]. Their results show that tourism has a positive and significant impact on the economic growth of Latin American countries.…”
mentioning
confidence: 99%
“…For example, Eugenio-Martín, Morales, and Scarpa (2004) have shown that tourism expansion is chiefly responsible for the economic growth of 21 Latin American countries. Using the Tourism Satellite Account model, Jovanović and Vukasović (2014) show a direct contribution of tourism consumption to Serbia's GDP.…”
Section: Literaturementioning
confidence: 99%
“…The contribution of tourism to development is explored by Eugenio-Martin et al [20] where they look at the relationship between tourism and economic growth. Using a panel data approach for Latin American countries for the period 1985-1998, their findings reveal that tourism is appropriate for economic growth of medium and low-income countries and not necessarily a sufficient factor for the developed world.…”
Section: Tourism Impact On Income Generation and Job Creationmentioning
confidence: 99%